2023
DOI: 10.3390/md21010039
|View full text |Cite
|
Sign up to set email alerts
|

N-3 PUFA Deficiency Aggravates Streptozotocin-Induced Pancreatic Injury in Mice but Dietary Supplementation with DHA/EPA Protects the Pancreas via Suppressing Inflammation, Oxidative Stress and Apoptosis

Abstract: It has been reported that dietary n-3 polyunsaturated fatty acids (n-3 PUFAs) exert therapeutic potential for the preservation of functional β-cell mass. However, the effect of dietary n-3 PUFA deficiency on pancreatic injury and whether the supplementation of n-3 PUFA could prevent the development of pancreatic injury are still not clear. In the present study, an n-3 PUFA deficiency mouse model was established by feeding them with n-3 PUFA deficiency diets for 30 days. Results showed that n-3 PUFA deficiency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 45 publications
0
1
0
Order By: Relevance
“…Further research measuring the β-cell apoptosis to proliferation ratios will be needed to confirm whether the increase in β-cell numbers in the Fish-HFDS group is not a compensatory mechanism against the diet-induced insulin resistance. Moreover, pre-intervention with fish oil has a favorable impact on islet morphology ( 42 ), which needs to be further evaluated in various settings.…”
Section: Discussionmentioning
confidence: 99%
“…Further research measuring the β-cell apoptosis to proliferation ratios will be needed to confirm whether the increase in β-cell numbers in the Fish-HFDS group is not a compensatory mechanism against the diet-induced insulin resistance. Moreover, pre-intervention with fish oil has a favorable impact on islet morphology ( 42 ), which needs to be further evaluated in various settings.…”
Section: Discussionmentioning
confidence: 99%
“…This result implies that insulin secretion was not completely recovered after 3 weeks of oral fish oil administration. In contrast, scientific studies reported that omega-3 fatty acids may improve insulin secretion ( Baynes et al ., 2018 ; Zou et al ., 2023 ). In the cell culture study, fish oil can prevent pancreatic cell death and enhance insulin secretion ( Wei et al ., 2010 ; Das et al ., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…After the administration of n-3 PUFAs, in vitro immunofluorescence and mRNA expression studies have shown increased expression of antioxidant-related genes like Sirt1 and Bcra1/Msh2, which are key in DNA repair [170]. These FA nutrient effects have already been widely studied in numerous pathologies, like metabolic syndrome, cardiovascular disease [171], chronic obstructive pulmonary disease (COPD) [172], pancreatic problems [173], and endocrinal and sexual conditions like polycystic ovaries [170], among others. One limitation noted in our literature search is that placental oxidative stress conditions has been less explored; therefore, future clinical trials should rely on available data from animal models.…”
Section: Polyunsaturated Fatty Acidsmentioning
confidence: 99%